Identificação de danos em vigas via análise modal - Lima Júnior, Wiu José de (2020)
This research seeks to contribute in the Field of damage identification in beams based on modal properties, proposing sensitivity studies on two numerical models, which will be elaborated in commercial finite element software: a simply supported simple concrete beamand a fixed-end steel beam, which purpose is to evaluate the reliability of three methods to identification single and multiple damages: (1) Changes in Curvature Mode Shapes, (2) Mode Shape Data Based Indicator, (3) Modal Strain Energy Change and (4) Reformulated Modal Strain Energy Change, it is also proposed the modification of the first two methods. The results obtained showed that the Modal Strain Energy Change method, despite the difficulty existing in the practice of engineering, identified the damage correctly, the Reformulated Modal Strain Energy Change method proved promising and the modified methods proposed presented better performance in relation to the originals.